Ecotribology Research Developments - Davim, J. Paulo (Materials Forming, Machining and Tribology,, 2016)
This book presents resent research advances in the area of eco-triobology. In the last years, eco-tribology or environmentally friendly tribology has gained increasing importance in sustainable engineering. Environmentally acceptable tribological practices save resources by optimizing product usage and reducing energy. This book covers current developments in all areas covered by the term eco-tribology, including biomimetics surfaces, control of friction and wear, environmental aspects of lubrication and surface modification techniques as well as tribological aspects of green applications, such wind-power turbines or solar panels.